Tissue‐based quantitative proteomics to screen and identify the potential biomarkers for early recurrence/metastasis of esophageal squamous cell carcinoma - Xu‐Wei Cai; Wei‐Wei Yu; Wen Yu; Qin Zhang; Wen Feng; Mi‐Na Liu; Meng‐Hong Sun; Jia‐Qing Xiang; Ya‐Wei Zhang; Xiao‐Long Fu (Cancer Medicine, 2018)
Abstract Esophageal squamous cell carcinoma (ESCC) is the eighth cause of cancer‐related deaths worldwide. To screen potential biomarkers associated with early recurrence/metastasis (R/M) of ESCC patients after radical resection, ESCC patients were analyzed by a comparative proteomics analysis using iTRAQ with RPLC‐MS to screen differential proteins among R/M groups and adjacent normal tissues. The proteins were identified by qRT‐PCR, Western blotting, and tissue microarray. The protein and mRNA expression difference of PHB2 between tumor tissues of ESCC patients and adjacent normal tissues, ESCC patients with and without metastasis, four ESCC cell lines and normal esophageal epithelial cells were inspected using immunohistochemical staining, qRT‐PCR, and Western blotting. The EC109 and TE1 cells were used to establish PHB2 knockdown cell models, and their cell proliferation and invasion ability were determined by cell counting method, Transwell® assay. Thirteen proteins were selected by cutoff value of 0.67 fold for underexpression and 1.5‐fold for overexpression. Seven proteins were confirmed to be associated with R/M among the 13 proteins. The potential biomarker PHB2 for early recurrence/metastasis of ESCC was identified. PHB2 expression was related to the OS of ESCC patients (P = 0.032) and had high levels in the tumor tissues and human cell lines of ESCC (P = 0.0002). Also, the high PHB2 expression promoted the metastasis of ESCC (P = 0.0075), suggesting high PHB2 expression was a potential prognostic biomarker. Experiments showed that PHB2 could significantly promote the proliferation and cell invasion ability of human ESCC cell lines and the knockdown of PHB2 suppressed the phosphorylation level of AKT, as well as the expression of MMP9 and RAC1. PHB2 could predict the early metastasis of ESCC patients.